2013
DOI: 10.1590/s1679-45082013000400011
|View full text |Cite
|
Sign up to set email alerts
|

Adequação dos parâmetros de oxigenação em idosos submetidos à ventilação mecânica

Abstract: Objective:To compare ideal PaO2 with PaO2 found, ideal PaO2/FiO2 of room air with the one found, and ideal FiO2 with FiO2 found in mechanically ventilated elderly patients.Methods:Cross-sectional study that evaluated elderly mechanically ventilated patients for at least 72 hours and who underwent three subsequent blood gas analyses.Results:The sample consisted of 48 elderly with mean age of 74.77±9.36 years. There was a significant difference between the ideal PaO2 and the one found (p<0.001), between FiO2 cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
(15 reference statements)
0
4
0
4
Order By: Relevance
“…The PaO 2 /FiO 2 ratio is often one of the indicators to determine whether a critically ill patient is under prolonged mechanical ventilation. [15][16][17] The findings showed that early PaO 2 /FiO 2 was not a risk factor for prolonged mechanical ventilation. These rather intriguing findings could be attributed to as follows: First, lower oxygenation in the early stage of severe burn patients is mainly caused by upper respiratory tract obstruction, but respiratory tract obstruction is less likely to occur within 12 h after inhalation injury or facial and neck ring burn injury.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The PaO 2 /FiO 2 ratio is often one of the indicators to determine whether a critically ill patient is under prolonged mechanical ventilation. [15][16][17] The findings showed that early PaO 2 /FiO 2 was not a risk factor for prolonged mechanical ventilation. These rather intriguing findings could be attributed to as follows: First, lower oxygenation in the early stage of severe burn patients is mainly caused by upper respiratory tract obstruction, but respiratory tract obstruction is less likely to occur within 12 h after inhalation injury or facial and neck ring burn injury.…”
Section: Discussionmentioning
confidence: 87%
“…The PaO 2 /FiO 2 ratio is often one of the indicators to determine whether a critically ill patient is under prolonged mechanical ventilation 15–17 . The findings showed that early PaO 2 /FiO 2 was not a risk factor for prolonged mechanical ventilation.…”
Section: Discussionmentioning
confidence: 98%
“…Um dos pontos mais importantes na formação de um engenheiro é entender como funciona a deflexão. Segundo Gere (2003), esse processo possui grande relevância prática, sendo essencial e básico em um projeto de vigas na construção civil e também são importantes em análises dinâmicas, como na verificação de vibrações de aeronaves ou nas respostas de edifícios aos terremotos.…”
Section: Curva De Deflexãounclassified
“…Como o eixo 𝑦 é positivo para cima, a deflexão também será positiva sempre que se manifestar para cima. (GERE, 2003). Fonte: (GERE -adaptada, 2003).…”
Section: Curva De Deflexãounclassified
“…It should be noted that the high prevalence of respiratory failure requires the need for further studies on the adequacy of inspired oxygen fractions, since acute respiratory insufficiency almost always evolves to mechanical ventilation and consequently to the administration of supplementary oxygen, which if misused, may lead to toxic effects. 19 In a study that aimed to understand the experiences of the hospitalization process in an ICU, the elderly patients and their relatives reported that the greatest distress refers to the lack of information about the health status of hospitalized elderly people. So, there should be investment in professional training for the geriatrics and gerontology areas, which may contribute to increase the quality of care provided to this population.…”
Section: Aspiration Of Secretionsmentioning
confidence: 99%